2021
DOI: 10.1111/ctr.14216
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID‐19 in hospitalized solid organ transplant recipients compared to a matched cohort of non‐transplant patients at a national healthcare system in the United States

Abstract: Data describing outcomes of solid organ transplant (SOT) recipients with coronavirus disease 2019 (COVID‐19) are variable, and the association between SOT status and mortality remains unclear. In this study, we compare clinical outcomes of SOT recipients hospitalized with COVID‐19 between March 10, and September 1, 2020, to a matched cohort of non‐SOT recipients at a national healthcare system in the United States (US). From a population of 43 461 hospitalized COVID‐19‐positive patients, we created a coarsened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
69
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 33 publications
6
69
0
3
Order By: Relevance
“…Solid organ transplant recipients (SOTR) are at risk for poor outcomes from coronavirus disease 2019 (COVID‐19) due to the frequent medical comorbidities and the potential impact of immunosuppression 1,2 . Lung transplant recipients (LTR) with COVID‐19 are unique among SOTR because severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) directly infects the allograft.…”
Section: Introductionmentioning
confidence: 99%
“…Solid organ transplant recipients (SOTR) are at risk for poor outcomes from coronavirus disease 2019 (COVID‐19) due to the frequent medical comorbidities and the potential impact of immunosuppression 1,2 . Lung transplant recipients (LTR) with COVID‐19 are unique among SOTR because severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) directly infects the allograft.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Kidney transplant (KT) recipients is a subset of the population at high risk of severe COVID-19 relate consequences due to comorbidities, consequences of chronic kidney disease (CKD) and the burden of immunosuppressive therapy (IST), which in some subjects include also therapies administered before kidney transplantation to treat glomerulonephritis or underlying autoimmune diseases. [2] Data collected so far reported that transplant recipients were at higher risk of morbidity and mortality compared to the general population [3,4]. Despite the great emphasis on IST reduction to face the potentially lethal consequences of COVID-19, no confirming data supports its beneficial effect in terms of survival or clinical and laboratory manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…Data collected so far reported that transplant recipients were at higher risk of morbidity and mortality compared to the general population [3,4]. Despite the great emphasis on IST reduction to face the potentially lethal consequences of COVID-19, no confirming data supports its beneficial effect in terms of survival or clinical and laboratory manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…1 SOT recipients were found to have higher mortality and were more likely to require mechanical ventilation, vasopressor support, and develop acute kidney injury when compared to their non-SOT counterparts. 2,3 Mortality in SOT recipients hospitalized for COVID-19 can be up to 20%. 4 Due to these concerns, there was a 51.1% reduction in overall deceased donor transplantation in the USA since the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%